A Theory of Constitutional Horizontality in Ireland - Gilligan, Daniel (Trinity College Dublin. School of Law. Discipline of Law, 2025)
In modern legal systems, constitutional rights core domain of legal operation is the vertical relation between the State and private persons. Constitutional horizontality names that phenomenon whereby constitutional rights acquire legal significance for the horizontal legal relations between private persons inter se. The topic of this thesis is the Irish law of constitutional horizontality. Its central research question is: is that law justified? Its answer is a longwinded, qualified, and (in a sense to be explained) detached yes. When viewed in comparative relief, the Irish law of horizontality appears radical and idiosyncratic. At the same time, domestic scholarship on the topic has often resigned itself to the laws incoherence. In this context, this thesis reconsiders the normative underpinnings of this area of law, searching for a standpoint from which its basic shape can be seen to make sense. The argument proceeds from a simple, familiar, and powerful moral principle, the details of which I work up over the course of the thesis: no one is anyone elses subordinate. I argue that taking this moral principle seriously as a basic constitutional one can make the courts key doctrinal choices in this area seem natural rather than awkward, perceptive rather than arbitrary, and (on the whole) justified. That is, the principle can be seen to undergird and unify the horizontal significance(s) constitutional rights have had in Irish law. It can account for the sharp limits to that significance. And it vindicates the sense in which certain aspects of private persons legal relations with one another are, indeed, properly constitutional in character.
APPROVED
Keywords: Private Law; Constitutional Law; Human Rights; Legal Philosophy; Horizontal Effect